CONTRIBUTION OF RESERVATION THROUGH TRAVEL AGENT TO ROOM OCCUPANCY AT LE GRANDE BALI - Ni Made Novi Cipta Dewi; I Nyoman Rajin Aryana; Ni Made Ernawati; Ni Nyoman Sri Astuti; I Ketut Suarta (Journal of Applied Sciences in Travel and Hospitality, 2018)
Travel agent is a business engaged in the field of service and provides information about all things related to travel. The purpose of this study is to find out how the application of travel agent reservation with room occupancy at Le Grande Bali and to know the comparison of travel agent reservation and room occupancy at Le Grande Bali. The rationale to discuss this topic in this research with the title "Contribution Of Reservation Through Travel Agent To Room Occupancy At Le Grande Bali" because the existence of travel agent is very supportive to tourism progress in Bali especially in Hotel Le Grande Bali. Meanwhile, the data used is reservation data through travel agent and room occupancy from January to December 2015 – 2017 and January to April 2018. The theory used in this research is the theory of travel agent, understanding of reservation and theory about the review of occupancy rate room. Data in this research is obtained through data collection method that is interview, documentation, observation and literature study. Then, data analysis method used is qualitative descriptive method. Based on the results of this study, it showed that the development of the travel agent reservation rate with the hotel room occupancy rate was decreasing. The highest travel agent reservation rate was in July to October while the highest occupancy rate was in July to August. It is due to the reason that it was a high season.